Telomerase Interaction Partners-Insight from Plants - Fulnečková, Jana; Dokládal, Ladislav; Kolářová, Karolína; Nešpor Dadejová, Martina; Procházková, Klára; Gomelská, Sabina; Sivčák, Martin; Adamusová, Kateřina; Lyčka, Martin; Peska, Vratislav; Dvořáčková, Martina; Sýkorová, Eva (International journal of molecular sciences, 2021)
Telomerase, an essential enzyme that maintains chromosome ends, is important for genome integrity and organism development. Various hypotheses have been proposed in human, ciliate and yeast systems to explain the coordination of telomerase holoenzyme assembly and the timing of telomerase performance at telomeres during DNA replication or repair. However, a general model is still unclear, especially pathways connecting telomerase with proposed non-telomeric functions. To strengthen our understanding of telomerase function during its intracellular life, we report on interactions of several groups of proteins with the Arabidopsis telomerase protein subunit (AtTERT) and/or a component of telomerase holoenzyme, POT1a protein. Among these are the nucleosome assembly proteins (NAP) and the minichromosome maintenance (MCM) system, which reveal new insights into the telomerase interaction network with links to telomere chromatin assembly and replication. A targeted investigation of 176 candidate proteins demonstrated numerous interactions with nucleolar, transport and ribosomal proteins, as well as molecular chaperones, shedding light on interactions during telomerase biogenesis. We further identified protein domains responsible for binding and analyzed the subcellular localization of these interactions. Moreover, additional interaction networks of NAP proteins and the DOMINO1 protein were identified. Our data support an image of functional telomerase contacts with multiprotein complexes including chromatin remodeling and cell differentiation pathways.
Keywords: Ribosomes; Golgiho aparát; Telomere Homeostasis; telomerase; transport; posttranskripční úpravy RNA; Arabidopsis Proteins; Telomerase; Mitochondria; vazba proteinů; homeostáza telomer; Transcription, Genetic; telomerasa; replikace DNA; protein–protein interaction; Golgi Apparatus; mitochondria; Protein Binding; Protein Interaction Maps; Chromatin Assembly and Disassembly; Telomere-Binding Proteins; proteiny huseníčku; mapy interakcí proteinů; mitochondrie; peptidy; genetická transkripce; folding; RNA Processing, Post-Transcriptional; proteiny vázající telomery; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; restrukturace chromatinu; chromatin; nukleozomy; Multiprotein Complexes; ribozomy; replication; Arabidopsis; DNA Replication; Nucleosomes; Peptides; multiproteinové komplexy